2009
DOI: 10.1186/1476-069x-8-8
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of non-invasively collected matrices for human biomonitoring

Abstract: With its inclusion under Action 3 in the Environment and Health Action Plan 2004–2010 of the European Commission, human biomonitoring is currently receiving an increasing amount of attention from the scientific community as a tool to better quantify human exposure to, and health effects of, environmental stressors. Despite the policy support, however, there are still several issues that restrict the routine application of human biomonitoring data in environmental health impact assessment. One of the main issue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
56
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(57 citation statements)
references
References 89 publications
(110 reference statements)
1
56
0
Order By: Relevance
“…Compared to forensic and clinical fields, little is known about hair analysis for determination of persistent organic pollutants (POPs) [56,57]. Hair analysis has been explored for polychlorinated dibenzo-p-dioxins (PCDDs) and polychlorinated dibenzofurans (PCDFs) [58][59][60], polychlorinated biphenyls (PCBs) [61][62][63][64], pesticides [62,65,66], and PBDEs [67][68][69].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to forensic and clinical fields, little is known about hair analysis for determination of persistent organic pollutants (POPs) [56,57]. Hair analysis has been explored for polychlorinated dibenzo-p-dioxins (PCDDs) and polychlorinated dibenzofurans (PCDFs) [58][59][60], polychlorinated biphenyls (PCBs) [61][62][63][64], pesticides [62,65,66], and PBDEs [67][68][69].…”
Section: Introductionmentioning
confidence: 99%
“…These include maternal and fetal blood, and milk from the general population in South China (Bi et al 2006), blood serum from e-waste workers in South China (Qu et al 2007), and hair of residents living at an e-waste site in Southeast Zhejiang Province (Zhao et al 2008); PBDE levels were found to be significantly higher than those from reference sites. Hair serves as a noninvasive matrix for the biomonitoring of pollutants (Smolders et al 2009), and breast milk provides information on exposure levels of both the mother and her child (Esteban & Castaño 2009). To date, there are very limited studies of PBDE body burden with regard to the concurrent analyses of multiple human matrices.…”
Section: Introductionmentioning
confidence: 99%
“…Even at low levels, PBDEs and PCBs can exert undesirable effects on wildlife and human beings. Emergent evidence from biomonitoring program suggested that PBDEs and PCBs, similar to other persistent organic pollutants (POPs), exert certain degree of neurological, endocrine-disrupting, immune-disrupting and genotoxic effects [15][16][17][18]. Therefore, these compounds have been included in biomonitoring programs as well as National Health and Nutrition Examination Survey (NHANES) held by Centers for Disease Control and Prevention (CDC) extensively.…”
Section: Introductionmentioning
confidence: 98%